2003
DOI: 10.1111/1467-8276.00121
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Technology, Risk Preferences, and Adoption of Site‐Specific Technologies

Abstract: A model of farmer decision making is developed to determine the extent to which uncertainties about soil fertility and weather affect the value of site‐specific technologies (SSTs) using jointly estimated risk and technology parameters. Uncertainty can lead risk‐averse farmers to apply more fertilizers and generate more pollution than in the certainty case. Ignoring uncertainty and risk aversion would overestimate the economic and environmental benefits of SSTs and underestimate the subsidy required to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
3
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 27 publications
6
67
3
1
Order By: Relevance
“…Since farmers are generally risk averse (e.g. Chavas and Holt, 1996;Lence, 2000;Isik and Khanna, 2003;Kumbhakar and Tveteras, 2003), and adverse outcomes can have large consequences for their welfare, they will try to mitigate these risks through input and output choices. Many farmers produce several outputs, and can be regarded as portfolio managers who, through input and output choices, balance the expected economic return and risk (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since farmers are generally risk averse (e.g. Chavas and Holt, 1996;Lence, 2000;Isik and Khanna, 2003;Kumbhakar and Tveteras, 2003), and adverse outcomes can have large consequences for their welfare, they will try to mitigate these risks through input and output choices. Many farmers produce several outputs, and can be regarded as portfolio managers who, through input and output choices, balance the expected economic return and risk (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This form of the variance function is due to (Harvey, 1976) and subsequently employed by several studies (Isik and Devadoss 2006, Isik and Khanna 2003, Asche and Tveteras 1999. The main advantage of this form is that it ensures positive output variance.…”
Section: Methodsmentioning
confidence: 99%
“…Previous results have shown that risk aversion will increase the adoption of a technology if it is risk reducing (Sandmo, 1971;Feder, 1980;Isik and Khanna, 2003;Koundouri, Nauges, and Tzouvelekas, 2006). Other than a few exceptions (Carey and Zilberman, 2002;Isik and Khanna, 2003;Koundouri, Nauges, and Tzouvelekas, 2006) much of this work measures the impact of uncertainty on the choice of capacity or capital (a continuous variable) and not on the choice between a small number of discrete technologies. In contrast to other articles our paper explicitly considers an individual's ability to temporarily suspend operations (we refer to this as the shutdown effect).…”
Section: Introductionmentioning
confidence: 97%